Development of a low resource exercise rehabilitation application for musculoskeletal disorders to help underserved patients in a primary care setting. - Edgar, Michael C.; Lambert, Cameron; Abbas, Anser; Young, James J.; McIsaac, Willem; Monteiro, Rhea; Girdhari, Rajesh; Schofield, Lee; Miller, Lisa; Kopansky-Giles, Deborah (Journal of the Canadian Chiropractic Association, 2022)
Objective: We set out to create a Family Medicine EHR (electronic health record) embedded exercise application. This was done to evaluate the utility of the exercise app for providers and to understand the usefulness of the exercise app from the perspective of patients. Methods: This exercise application was developed through an iterative process with repeated pre-testing and feedback from an interprofessional team and embedded into the EHR at an academic family medicine clinic. Anecdotal feedback from patients was used to inform pre-testing adaptations. Results: The application required six iterations prior to clinical utility. It had several features that clinicians and patients felt were beneficial. These features involved a customizable exercise directory with pre-made templated plans which could be further modified. To overcome accessibility barriers, the application was developed to include digital and printable copies with an integrated direct email option for ease of remote sharing with patients. Conclusion: A customizable, open-source exercise application was developed to facilitate provider exercise prescription and support patient self-management. This project may be useful for other providers interested in developing similar programs to address musculoskeletal conditions in their patients. Next steps are to undertake pilot testing of the app with broader provider and patient feedback.